Answer:
$21.25
Step-by-step explanation:
The cost of the 2 adult tickets before the discount is $8 * 2 = $16
The cost of the 2 child tickets before the discount is $5 * 2 = $10
The total cost before the discount is $16 + $10 = $26
The total cost after the discount is
$26 * (1 - 0.15) =
$26 * 0.85 =
$21.25
<h3>
Answers:</h3><h3>
6 quarters</h3><h3>
2 dimes</h3>
================================================
Work Shown:
d = number of dimes
q = number of quarters
q = d+4 since she has 4 more quarters than dimes
$1.70 = 170 cents
10d = value of all the dimes in cents
25q = value of all the quarters in cents
10d+25q = total value of all the coins in cents
10d+25q = 170
10d+25( q ) = 170
10d+25( d+4 ) = 170 .... plug in q = d+4
10d+25d+100 = 170 .... distribute
35d+100 = 170
35d = 170-100 ..... subtract 100 from both sides
35d = 70
d = 70/35 ... divide both sides by 35
d = 2
He has 2 dimes
q = d+4
q = 2+4
q = 6
He also has 6 quarters
------------------
Check:
1 dime = 10 cents
2 dimes = 20 cents ..... multiply both sides by 2
1 quarter = 25 cents
6 quarters = 150 cents ..... multiply both sides by 6
(2 dimes) + (6 quarters) = (20 cents) + (150 cents) = 170 cents
This confirms the answers.
Example: Set up proportions.
3/4 cups → 1 batch
x cups → 2 batches
x = 2(3/4) = 6/4 = 1 1/2 cups
3/4 cups → 1 batch
y cups → 9 batches
y = 9(3/4) = 6 3/4 cups
Answer:
x = 5 and value of y = 2
Step-by-step explanation:
using substitution method
let;
x + 4y = 13...................... equation 1
x - y = 3............................... equation 2
from equation 2
x - y = 3.................................... eqn 2
x = y + 3.......................................... equation 3
put x = y + 3 in equation 1
x + 4y = 13...................... equation 1
y + 3 + 4y = 13
5y = 13 - 3
5y = 10
divide both sides by 5
i.e
5y/5 = 10/5
y = 2
sustitue for y = 2 in equation 3
x = y + 3.......................................... equation 3
x = 2 + 3
x = 5
therefore the value of x = 5 and value of y = 2
to check if your answwer is correct slot in the value of x and y in any of the equation . e.g
from equation 3
x = y + 3.......................................... equation 3
5= 2 + 3
5 =5....................... proved
Answer:
the first four terms is 3, 0, -3, -6